Cardano's Formula/Real Coefficients
Theorem
Let $P$ be the cubic equation:
- $a x^3 + b x^2 + c x + d = 0$
with $a \ne 0$.
Let $a, b, c, d \in \R$.
Let $D$ be the discriminant of $P$:
- $D := Q^3 + R^2$
where:
- $Q = \dfrac {3 a c - b^2} {9 a^2}$
- $R = \dfrac {9 a b c - 27 a^2 d - 2 b^3} {54 a^3}$
Then:
- $(1): \quad$ If $D > 0$, then one root is real and two are complex conjugates.
- $(2): \quad$ If $D = 0$, then all roots are real, and at least two are equal.
- $(3): \quad$ If $D < 0$, then all roots are real and unequal.
Proof
From Cardano's Formula, the roots of $P$ are:
\(\text {(1)}: \quad\) | \(\ds x_1\) | \(=\) | \(\ds S + T - \dfrac b {3 a}\) | |||||||||||
\(\text {(2)}: \quad\) | \(\ds x_2\) | \(=\) | \(\ds -\dfrac {S + T} 2 - \dfrac b {3 a} + \dfrac {i \sqrt 3} 2 \paren {S - T}\) | |||||||||||
\(\text {(3)}: \quad\) | \(\ds x_3\) | \(=\) | \(\ds -\dfrac {S + T} 2 - \dfrac b {3 a} - \dfrac {i \sqrt 3} 2 \paren {S - T}\) |
where:
\(\ds S\) | \(=\) | \(\ds \sqrt [3] {R + \sqrt {Q^3 + R^2} }\) | ||||||||||||
\(\ds T\) | \(=\) | \(\ds \sqrt [3] {R - \sqrt {Q^3 + R^2} }\) |
Zero Discriminant
First the easy case: $D = 0$.
Hence $S = T = \sqrt [3] R$, and so $S + T = 2 \sqrt [3] R, S - T = 0$.
From the above, this gives us:
\(\text {(1)}: \quad\) | \(\ds x_1\) | \(=\) | \(\ds 2 \sqrt [3] R - \dfrac b {3 a}\) | |||||||||||
\(\text {(2)}: \quad\) | \(\ds x_2\) | \(=\) | \(\ds -\sqrt [3] R - \dfrac b {3 a}\) | |||||||||||
\(\text {(3)}: \quad\) | \(\ds x_3\) | \(=\) | \(\ds -\sqrt [3] R - \dfrac b {3 a}\) |
Thus the roots $x_2$ and $x_3$ are equal, and all three roots are real.
They are all equal when $R = 0$.
$\Box$
Positive Discriminant
Let $D = Q^3 + R^2 > 0$.
Then $S = R + \sqrt{Q^3 + R^2}$ and $T = R - \sqrt{Q^3 + R^2}$ are wholly real and distinct.
Therefore, so are $S + T$ and $S - T$.
Hence:
- $\dfrac {S + T} 2 - \dfrac b {3 a} + \dfrac {i \sqrt 3} 2 \paren {S - T}$
and
- $\dfrac {S + T} 2 - \dfrac b {3 a} - \dfrac {i \sqrt 3} 2 \paren {S - T}$
are complex conjugates.
$\Box$
Negative Discriminant
Let $D = Q^3 + R^2 < 0$.
Then $\sqrt D = \pm i \left|{Q^3 + R^2}\right| = \pm i E$, say, where $E > 0$.
Thus $S^3 = R + i E, T^3 = R - i E$.
Let $\sqrt [3] {R + i E} = p + i q$, and so $\sqrt [3] {R - i E} = p - i q$.
Hence $S + T = 2 p, S - T = 2 i q$.
So:
\(\ds y_1\) | \(=\) | \(\ds S + T\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds 2 p\) | ||||||||||||
\(\ds y_2\) | \(=\) | \(\ds -\dfrac {S + T} 2 + \dfrac {i \sqrt 3} 2 \paren {S - T}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds -p - \sqrt 3 q\) | after algebra | |||||||||||
\(\ds y_3\) | \(=\) | \(\ds -\dfrac {S + T} 2 - \dfrac {i \sqrt 3} 2 \paren {S - T}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds -p + \sqrt 3 q\) | after algebra |
Subtracting $\dfrac b {3 a}$ from the above, we obtain the three distinct real solutions:
\(\text {(1)}: \quad\) | \(\ds x_1\) | \(=\) | \(\ds 2 p - \dfrac b {3 a}\) | |||||||||||
\(\text {(2)}: \quad\) | \(\ds x_2\) | \(=\) | \(\ds -p - \sqrt 3 q - \dfrac b {3 a}\) | |||||||||||
\(\text {(3)}: \quad\) | \(\ds x_3\) | \(=\) | \(\ds -p + \sqrt 3 q - \dfrac b {3 a}\) |
$\blacksquare$
Sources
- 1964: Milton Abramowitz and Irene A. Stegun: Handbook of Mathematical Functions ... (previous) ... (next): $3$: Elementary Analytic Methods: $3.8$ Algebraic Equations: Solution of Cubic Equations: $3.8.2$
- 1968: Murray R. Spiegel: Mathematical Handbook of Formulas and Tables ... (previous) ... (next): $\S 9$: Solutions of Algebraic Equations: $9.3$ Cubic Equation
- 1998: David Nelson: The Penguin Dictionary of Mathematics (2nd ed.) ... (previous) ... (next): cubic
- 2008: David Nelson: The Penguin Dictionary of Mathematics (4th ed.) ... (previous) ... (next): cubic